GOOGLE CLASSROOM AS THE LATEST LEARNING MEDIA IN THE COVID-19 PANDEMIC PERIOD - Nuraini Sri Bina; Rahmi Ramadhani (JCES (Journal of Character Education Society), 2021)
Abstrak: Masa pandemik COVID-19 mengharuskan pembelajaran daring. Masalahnya bencana yang datang tiba-tiba menyebabkan guru-guru SD Darul Ilmi Murni kurang memiliki persiapan untuk mengatasi pembelajaran daring. Untuk itu kegiatan PKM dilaksanakan berupa workshop mengenai aplikasi Google Classroom kepada guru-guru SD Swasta Darul Ilmi Murni yang bertujuan untuk membantu guru membuat pembelajaran daring efektif dimasa pandemik COVID-19. Banyak peserta yang mengikuti kegiatan PKM ini adalah 15 orang guru dari SD Swasta Darul Ilmi Murni. Dari hasil test evaluasi praktek penerapan aplikasi Google Classroom diperoleh 85% guru berhasil membuat pembelajaran daring efektif menggunakan aplikasi google classroom. Guru-guru memiliki keterampilan untuk mengelola pembelajaran daring menggunakan Google Classroom. Prestasi siswa meningkat setelah guru menerapkan Google Classroom pada pembelajaran daring. Respon siswa, orang tua dan guru sangat baik terhadap media pembelajaran daring Google Classroom.Abstract:  The period of the COVID-19 pandemic requires online learning. The problem is that the sudden disaster caused the teachers of primary school Darul Ilmi Murni to be less prepared to handle online learning. For this reason, PKM activities are carried out in the form of workshops on the Google Classroom application for teachers of Darul Ilmi Murni Primary School which aims to help teachers make online learning effective during the COVID-19 pandemic. The number of participants participating in this activity was 15 teachers. From the results of the test evaluation of the practice of implementing the Google Classroom application, it was found that 85% of teachers succeeded in making online learning effective using the google classroom application. Teachers have the skills to manage online learning using Google Classroom. Student achievement increased after the teacher implemented Google Classroom in online learning. Student, parent and teacher responses are very good to Google Classroom online learning media.